Informed Consent and Refusal in Obstetrics: A Practical Ethical Guide. Issue 2 (June 2018) - Kotaska, A.
Abstract : ( Birth . 2017;44(3):195–199) When women refuse their provider's advice, it can cause ethical tension and compromise care. Caregivers may believe they are legally or ethically liable when women decline recommended treatment. This article examined the ethical and legal basis of informed consent in order to build trust between patients and providers and minimize risk in these situations.